Development of Online Booking System for Medical Clinic - Humaid, Abdulrahman Jamal; Ghazali, Rozaida Binti (Applied Information Technology And Computer Science, 2022)
Recently, increasing number of clinics has been an obvious trend in many countries. This is mainly because the needs to providing medical services to increasing patients due to various forms of diseases. Such scenario needs careful attentions from the clinic’s management in order to provide appropriate services to patients. One of the important tasks to ensure efficient health care services is booking for medical appointment. With increasing number of patients, a systematic appointment booking is crucial in order to provide an accurate and fast medical treatment to patients. Conventional way of booking appointments time consuming since it requires patients to go to the clinic, in which eventually resulting in an increase in cost and effort. To overcome such problem, the appointment booking system can be made online via the Internet. With an internet-based booking system, appointment booking can be done from anywhere and at any time without having to go to clinic, therefore is time- and cost-effective. This study develops an online booking system for First Scan Clinic in Yemen. The system has developed using PHP and HTML programing and prototype models to achieve the objectives. The system will facilitate the patient to book an appointment easily by entering their information and choosing the appropriate time for visiting the doctor. Therefore, this system also will help with time scheduling to avoid crowds inside the clinic by receive a limited number of patients per day. In addition to that, the website will provide an advices and guidance about health awareness for patients.